The impact of marital power on relational aggression - Madsen, Chelsea Amber (Kansas State University, 2012)
Little information is available on the use of relational aggression in adult romantic relationships. In a sample of 325 married couples (650 spouses) we assessed the use of relational aggression within couples married an average of approximately 18 years to learn more about relational aggression within this population. To understand a potential motivating factor for the use of relational aggression, marital power was also examined. Finally, to learn whether or not relationship satisfaction mediates the relationship between marital power and relational aggression, relationship satisfaction was measured and was found to be a significant mediating variable. Using the actor/partner interdependence model, we found that those who were dissatisfied in their relationships, regardless of perceived marital power, were more likely to use relational aggression. Additionally, those who were satisfied in their marriage were less likely to use relational aggression. Wives participated in more relational aggression than husbands and husbands perceived themselves as having more power and were more satisfied in the marriage. Implications and suggestions for clinicians are offered.
Keywords: Relational aggression; Marital power; Marital satisfaction; Marital aggression; Relationship satisfaction; Aggression; Psychology (0621)